2015
DOI: 10.1016/j.mod.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular protease stl functions to inhibit migration of v'ch1 sensory neuron during Drosophila embryogenesis

Abstract: Proper migration of cells through the dense and complex extracellular matrix (ECM) requires constant restructuring of the ECM to allow cells to move forward in a smooth manner. This restructuring can occur through the action of extracellular enzymes. Among these extracellular enzymes is the ADAMTS (A Disintegrin And Metalloprotease with ThromboSpondin repeats) family of secreted extracellular proteases. Drosophila stl encodes an ADAMTS protease expressed in and around the peripheral nervous system (PNS) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Previous literature on the other two Drosophila ADAMTSs ( AdamTS‐A and stl ), as well as previous reports on mammalian ADAMTSs, have indicated that the main function of these particular extracellular proteases is to restructure the ECM for morphogenetic processes (Blelloch et al, ; Cal, Arguelles, Fernandez, & Lopez‐Otin, ; Enomoto et al, ; Ismat, Cheshire, & Andrew, ; Lhamo & Ismat, ; Liu, ; McCulloch et al, ; Nakada et al, ; Nishiwaki, Hisamoto, & Matsumoto, ; Surridge et al, ; Wagstaff, Kelwick, Decock, & Edwards, ; Wei, Richbourgh, Jia, & Liu, ; Xie et al, ). Vein formation in the wing is due to cell fate, and not cell migration or cell shape changes (Blair, ; Fristrom et al, ; Murray et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous literature on the other two Drosophila ADAMTSs ( AdamTS‐A and stl ), as well as previous reports on mammalian ADAMTSs, have indicated that the main function of these particular extracellular proteases is to restructure the ECM for morphogenetic processes (Blelloch et al, ; Cal, Arguelles, Fernandez, & Lopez‐Otin, ; Enomoto et al, ; Ismat, Cheshire, & Andrew, ; Lhamo & Ismat, ; Liu, ; McCulloch et al, ; Nakada et al, ; Nishiwaki, Hisamoto, & Matsumoto, ; Surridge et al, ; Wagstaff, Kelwick, Decock, & Edwards, ; Wei, Richbourgh, Jia, & Liu, ; Xie et al, ). Vein formation in the wing is due to cell fate, and not cell migration or cell shape changes (Blair, ; Fristrom et al, ; Murray et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…54 Stall (stl) ADAMTS protease has been shown to potentially prevent overmigration of the v'ch1 sensory neuron in the peripheral nervous system (PNS) during embryogenesis. 60 Although the molecular mechanism still needs to be worked out, it has been suggested that Stl might release an inhibitory ligand, thereby allowing this ligand to bind its receptor and prevent further migration. Moreover, AdamTS-B negatively regulates wing vein formation in the adult wing, a process determined by cell fate and not cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AdamTS‐A was shown to keep neural cell lineages in place in the CNS, a function that involves ECM remodeling, but not cell migration 54 . Stall (stl) ADAMTS protease has been shown to potentially prevent over‐migration of the v'ch1 sensory neuron in the peripheral nervous system (PNS) during embryogenesis 60 . Although the molecular mechanism still needs to be worked out, it has been suggested that Stl might release an inhibitory ligand, thereby allowing this ligand to bind its receptor and prevent further migration.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, however, the contribution of migration to the formation of insect nervous systems was under-appreciated. Although the differentiation of the embryonic CNS in insects typically involves relatively small displacements of newly generated neurons from their neurogenic niches [15, 16•], more dramatic patterns of neuronal and glial migration have now been documented in both the embryonic PNS [17] and the developing adult CNS [18,19, 20••]. A particularly striking example of migration was recently identified in the developing adult visual system of Drosophila, during which streams of newborn neurons travel into the optic lobes of the brain to establish discrete layers of interneurons with position-specific characteristics [21•, 22••, 23••].…”
Section: Introduction: Neuronal Migration and The Formation Of The Inmentioning
confidence: 99%